Assessment of self-rated consumer knowledge among low income housing residence in Malaysia - Haron, Sharifah Azizah; Masud, Jariah (Universiti Putra Malaysia Press, 2012)
Data from the 2008 Consumer Empowerment in a Globalized Market were used to examine factors associated with giving good self-rating on consumer knowledge and to identify the gap between self-rated and actual consumer knowledge among low income housing residence in Selangor and the Federal Territory of Kuala Lumpur. Those who claimed to know their rights and responsibilities as consumers and knew about the Consumer Protection Act 1999 are more likely to have good self-rated consumer knowledge. However, those in the lowest 20% income quintile and middle 20% income quintile are less likely than the top 20% income quintile to have good self-rated consumer knowledge. A high percentage of the respondents knew about and correctly stated their rights and responsibilities as consumers. On the contrary, only a few knew about the legislation that protected consumers and redress mechanism, indicating that they were not quite well-versed with a ‘higher level’ of consumer knowledge which is vital for their empowerment in the marketplace.